Efficacy of 577-nm retinal pigment epithelium laser photocoagulation in age-related maculopathy patients with various extents of morphological and functional loss (Ukrainian Journal of Ophthalmology, 2026)
Background: There is no unanimously adopted approach to titrating laser settings in subthreshold retinal laser photocoagulation (LPC) without ophthalmoscopically visible fundus changes. The efficacy of this approach to treatment of retinal diseases is still to be investigated.Purpose: To investigate the efficacy of 577-nm RPE LPC in the treatment of age-related maculopathy (ARM) with various extents of morphological and functional loss.Materials and Methods: The study involved 57 patients (57 eyes) diagnosed with ARM. 577-nm micropulse laser photocoagulation was applied to the RPE at the macula. Patients were followed-up for 12 months.Results: Three groups of ARM eyes with a similar extent of morphological and functional loss at baseline were created using Ward’s clustering method. Changes in visual acuity, retinal foveal thickness diameter and height of macular drusen, as well as incidences of subretinal neovascularization (SNV) and geographic atrophy over the follow-up for the groups were investigated. We observed no cases of SNV or geographic atrophy during the follow-up.Conclusions: 577-nm micropulse RPE laser photocoagulation with power titrated in micropulse mode was found to be efficacious and safe treatment for ARM patients with a wide variation in the extent of morphological and functional loss, including patients with drusenoid pigment epithelium detachment.
Keywords: micropulse laser photocoagulation; retinal pigment epithelium; age-related maculopathy